Phytoseiid mites of the tribes Afroseiulini, Kampimodromini and Phytoseiulini, and complementary notes on mites of the tribes Euseiini and Neoseiulini (Acari: Phytoseiidae) from sub-Saharan Africa - de Moraes, Gilberto J.; Zannou, Ignace D.; Ueckermann, Eddie A.; Oliveira, Anibal R.; Yaninek, John S.; Hanna, Rachid (Zootaxa, 2007)
This is the sixth publication in a series on the phytoseiid mites of sub-Saharan Africa. Seventeen phytoseiid species are reported in this paper, including all species of the Afroseiulini, Kampimodromini and Phytoseiulini known to occur in sub-Saharan Africa, in addition to one species of Euseiina and two species of Neoseiulini. Species of the latter two groups complement the respective lists of species presented in previous publications in this series. One species, Paraphytoseius ghanaensis n. sp., is described for the first time and four species are redescribed. Keys are included to help in the separation of the species in each tribe or subtribe.